ALADDIN AS AN IMMORAL ETHICIST IN ALADDIN AND THE MAGIC LAMP - Kahambing, Jan Gresil de los Santos; Duque, Anne Dominique (International Journal of Humanity Studies (IJHS), 2019)
This study delves into the tale Aladdin and the Magic Lamp as the excerpt of the Middle Eastern folk tales collection One Thousand and One Nights rather than the popular Disney version. It problematizes the figure of Aladdin and rebrands him as an immoral ethicist as opposed to Disney hero who seeks strength within himself and the other text versions of him as a â€œchangedâ€ man. This problematizing essentially entails a critique of the Westernized moral figure and its basic â€˜universal lessonâ€™ in the text to argue his being immoral. To do this, the methodology of the paper follows from a philosophical reading that subjectivizes the protagonist into the question of ethics. Specifically, it takes from Å½iÅ¾ekâ€™s elaboration of the Nietzschean version of an immoral ethics that remains consistent with the fidelity to oneâ€™s desire. The paper shows how the plot reveals Aladdinâ€™s immoral ethics that is founded on strength and constant activity but presupposing the voluntary knowledge and cleverness of his existential choice. To back this, the study finds three distinct features, namely: 1) disregard to authority, 2) love beyond good and evil, and 3) negative will to power.DOI:Â 10.24071/ijhs.2019.030108 Â